Language Features Comprehension in Reading Text and Problem Encountered by English Teacher - Bunau, Eusabinus (Jurnal Pendidikan Progresif, 2023)
Language Features Comprehension in Reading Text and Problem Encountered by English Teacher. Objectives: This research aimed to measure the frequency of language features comprehension in reading text and describe the problem encountered. Words and their class, like verbs, nouns, adjectives, adverbs, and their sub-classifications, including linking words and conjunction, are the instances of language features. Methods: This research used a survey involving 97 participants from senior high school English teachers purposively clustered from the population attending a professional in-service training program. A questionnaire consisting of 12 items with four options was used to measure the frequency of language features comprehension. The option to categorize the frequency was never, seldom, often, and always. Besides employing the questionnaire, an interview was also applied to explore the problem encountered by the English teachers when they administered their instructions. The survey result was analyzed using the relative frequency distribution formula, and the interview data were used to enrich the description in the discussion. Findings: Based on the computation, it was found that the frequency of language features comprehension of reading text surveyed through this research was 57.04% and distributed relatively into the Often Category, in which the category scale was 50%-75%. The comprehension frequency's mean score and standard deviation were 62.07 and 19.23. Conclusion: Despite the frequency and category, the interviewed participants asserted that they needed to be aware of the language features when linguistically termed vocabulary and morphology. This research infers more language features comprehension in reading texts frequently. Keywords: frequency, language features comprehension, reading text.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202320